Airline baggage fees and flight delays: A floor wax and dessert topping?. (August 2017) - Yazdi, Amirhossein A.; Dutta, Pritha; Steven, Adams B.
Highlights: Baggage fees are associated with improvement in on-time performance. It affects service quality directly, and indirectly via ticket prices and passenger demand. Its implementation is a "floor wax and dessert topping". It raises revenues for airlines, and it reduces sorting and loading complexities for airports. It improves on-time performance for air travelers. Abstract: We examine the linkages between the implementation of baggage fees and late flights in the airline industry. We find that baggage fees policies result in improvements in on-time performance as assessed through late flights, directly through improvements in airport-side sorting and loading efficiencies, and indirectly through lower air travel demand. We further find that these relationships are contingent upon the presence of a hub airport on a route. Our findings have important managerial and public policy implications as baggage fees have often been cited as a driver of security queue, aircraft alley, and overhead bin congestions, and ultimately delayed flights. Our results suggest that these suppositions could be misplaced.